ACCOUNTANCY: CIRCA 2000 A. D. - Smith, C. Aubrey (The Accounting Review, 1954)
Today no one is permitted to practice accounting as a profession, which includes the right to represent client or employer on accounting matters before any public body or to hold himself out as a public accountant, who has not been licensed by a state board of accountancy. There are some 262,000 individuals who have secured this license which goes by the old initials of C.P.A. but stands for Certified Professional Accountant and not Certified Public Accountant. This designation appears to have been a compromise as a result of the non-C.P.A. group's aggressive action in attempting to force all types of accounting practice under the licensing power of the states. Auditing as a technique and as a profession had reached the age of maturity. Auditing standards which had been discussed profusely and followed about as each practitioner pleased, in the middle of the 20th century, had become rules of practice any deviation from which was grounds for prompt disciplining of the offender. Inasmuch as the public had never fully understood how the C.P.A. could be independent on one engagement such as an audit, and yet serve in the capacity of a solicitor in a tax engagement or a consultant on matters of management services, every report must now state whether the engagement was conducted on the basis of that of an independent accountant or otherwise.